Chronic heart failure patients' experiences of German healthcare services: a protocol for a scoping review. Issue 2 (5th February 2019) - Dieckelmann, Mirjam; Reinhardt, Felix; Jeitler, Klaus; Semlitsch, Thomas; Plath, Jasper; Gerlach, Ferdinand M; Siebenhofer, Andrea; Petersen, Juliana J
Abstract : Introduction: Chronic heart failure (CHF) is a heterogeneous condition requiring complex treatment from diverse healthcare services. An increasingly holistic understanding of healthcare has resulted in contextual factors such as perceived quality of care, as well as patients' acceptance, preferences and subjective expectations of health services, all gaining in importance. How patients with CHF experience the use of healthcare services has not been studied within the scope of a systematic review in a German healthcare context. The aim of this scoping review is therefore to review systematically the experiences of patients affected by CHF with healthcare services in Germany in the literature and to map the research foci. Further objectives are to identify gaps in evidence, develop further research questions and to inform decision makers concerned with improving healthcare of patients living with CHF. Methods and analysis: This scoping review will be based on a broad search strategy involving systematic and comprehensive electronic database searches in MEDLINE, EMBASE, PsycINFO, PSYNDEX, CINAHL and Cochrane's Database of Systematic Reviews, grey literature searches, as well as hand searches through reference lists and non-indexed key journals. The methodological procedure will be based on an established six-stage framework for conducting scoping reviews that includes two independent reviewers. Data will be systematically extracted, qualitatively and quantitatively analysed and summarised both narratively and visually. To ensure the research questions and extracted information are meaningful, a patient representative will be involved. Ethics and dissemination: Ethical approval will not be required to conduct this review. Results will be disseminated through a clearly illustrated report that will be part of a wider research project. Furthermore, it is intended that the review's findings should be made available to relevant stakeholders through conference presentations and publication in peer-reviewed journals (knowledge transfer). Protocol registration in PROSPERO is not applicable for scoping reviews.